Pengaruh penerapan LKS berbasis conceptual understanding procedures (CUPS) terhadap kompetensi belajar IPA siswa kelas VII SMPN 3 Lengayang - nanda perdana putra; Dra.Yurnetti,M.Pd Yurnetti (PILLAR OF PHYSICS EDUCATION, 2019)
Achieving the competencies of students in science subjects has not shown optimal results because students are not accustomed to finding, searching for, and solving their own concepts learned, but only listening and writing what is conveyed by the teacher. Teachers often deliver learning material by lecture methods rather than practicing in the laboratory. In addition, students still depend on what is conveyed by the teacher and the low interest or willingness of students to read can also lead to low competency of students. Assessment activities that still focus on the final assessment must be changed to authentic assessment, where authentic assessment assesses from the preparation, process, and final results of learning activities. Therefore, researchers chose to use the Conceptual Understanding Procedures (CUPS) model with authentic assessments to be able to improve students' competencies. This research is limited to heat and energy material which aims to investigate the effect of the application of the CUPS model on increasing the competency of VII grade students in SMP 3 Lengayang.The type of research conducted is Quasy Experiment Research with the design of Randomized Control Group Only Design. The population of this study was VII grade students of SMP 3 Lengayang who were enrolled in the odd semester of the 2017/2018 academic year. Sampling is done by purposive sampling technique. Knowledge competency data were obtained through written tests. Data obtained were analyzed using two similarity tests on average.The results showed that knowledge competency data, the average experimental class 78.36 was higher than the control class 70.26. The data is normally distributed and the variance is homogeneous, so that the two similarity tests are carried out on average with the t-test, obtained tcount = 2,378 and t table = 2,019. It can be concluded that the application of LKS is based on the CUPS model by giving an influence on increasing the achievement of science competencies of the seventh grade students of SMP 3 Lengayang on all three competencies